Titik Kritis Kehalalan Bahan Tambahan Pakan (Feed Additive): Sebuah Tinjauan Pustaka - Lestariningsih Lestariningsih; Selania Nova; Arum Ayu Lestari (Universitas Nahdlatul Ulama Blitar, 2026)
The increasing awareness of Muslim consumers towards halal products necessitates the identification of halal critical points in feed additives used in the livestock industry. This research aims to identify halal critical points in various types of feed additives, analyze Islamic legal aspects related to their use, and provide safer alternative recommendations from a sharia perspective. A library research method was employed with literature searches through Google Scholar, ScienceDirect, and Portal Garuda using keywords related to feed additives and halal status, with inclusion criteria of publications from the last 10 years and MUI fatwas. Data were analyzed descriptively by comparing technical and Islamic legal aspects. The results show that feed additives from animal sources have the highest halal risk as they may originate from bones, blood, or organs of non-halal animals, microbial sources have critical points in fermentation media potentially using pork peptone, while synthetic sources require verification of processing aids such as anti-caking agents and emulsifiers. The use of feed containing haram ingredients can cause livestock to have jallalah status which is makruh for consumption. Phytobiotics from plants such as turmeric, ginger, garlic, and moringa can be safer alternatives from a sharia perspective with comparable effectiveness based on various studies. This study integrates technical aspects of feed additive production with Islamic legal perspectives including the concepts of istihalah and jallalah, and recommends the development of standardized phytobiotic formulations and comprehensive halal certification systems for the entire livestock feed production chain.